Analytic Analysis of a Cam Mechanism. (2017) - Hejma, Petr; Svoboda, Martin; Kampo, Jan; Soukup, Josef
Abstract: Cam mechanisms are integral parts of many products. They are used in many applications from combustion engines through milling machines to fitness machines. As suggested by their range of applications, it is an important issue. In this article the configuration of a mechanism, comprising a flat faced follower, which is pressed to the surface of a radial cam by the coil spring, is studied. On the basis of the known lifting function (the results of previous work) a new cam profile will be proposed. Lifting functions are of a polynomial character. Particularly, a cubic polynomial, the fifth degree polynomial and the seventh degree polynomial will be studied. Subsequently, there will be proposed a methodology for the calculation of torque according to the desired angular velocity of the cam. This methodology will be used for choosing a suitable electric motor and for a proper selection of coil springs. The spring preload will be determined with intention to avoid the rebound of the follower from the cam surface. Based on the analytical analysis a new measuring stand will be proposed. In future, the analytical results will be complemented by experiment.